The Europeanization of metropolitan regions from below: comparing the European engagement of two archetypical metropolises - Fricke, Carola (2021)
Abstract: Since the early 2000s, the Europeanization of metropolitan regions from below takes place in a political process with variable geometry and differential intensity. While ‘the metropolitan’ as a political label and research topic has witnessed an impressive upswing in Europe, a concrete understanding of the Europeanization of metropolitan regions is still missing. This article highlights and explains the Europeanization of metropolitan regions in Europe as particular subnational authorities of which only a small group of forerunners recently develop the capacity to act at a European scale. The Europeanization of metropolitan regions is conceptualized as a political process from below, going beyond the initial definition of Europeanization as domestic impact. Thereby, the article lays particular focus on ‘where’ and ‘when’ the European dimension of metropolitan regions is produced. Moreover, the analysis puts the emerging European engagement of metropolitan regions into a larger perspective by discussing it in the context of the increasing international agency of cities. The article questions, first, how a European dimension has developed in metropolitan policies and, second, what modes of engagement contribute to the metropolitan regions’ increasing Europeanization. Empirically, the metropolitan regions of Lyon and Stuttgart present examples of Europeanized metropolises with an exceptional engagement. Comparing modes of engagement in these two metropolitan regions allows understanding the particular characteristics contributing to the formation of an archetype of Europeanized metropolis